Unraveling Advanced Glycation End Products: Mechanisms, Pathophysiology, and Emerging Natural Therapeutic Interventions - Macwan, Dipeksha; V. Patel, Hiteshkumar (Pharmacognosy Reviews)
Protein glycation is an emerging issue that needs attention because it presents a hazard to the health of individuals. Through a sequential succession of non-enzymatic biochemical reactions occurs during glycation of protein, Advanced Glycation End products (AGEs) are formed which makes proteins nonfunctional and through accumulation in the body leading to serious pathogenic conditions. Their accumulation is accelerated in hyperglycemic and oxidative environments, linking them closely to chronic diseases such as diabetes, cardiovascular disease, neurodegenerative disorders, and kidney dysfunction. AGEs exert their pathological effects through direct cross-linking of extracellular matrix proteins and interaction with cell-surface receptors, particularly the Receptor for AGEs (RAGE). However, there are several substances that can be used to diminish the development of AGEs and the problems brought through glycated proteins. These synthetic antiglycation drugs have ineffective pharmacological outcomes and limited efficacy. Utilizing bioactive substances from natural sources is a better strategy to treat glycation-related issues and to prevent AGEs-associated pathogenesis since they have fewer adverse effects and are more effective. In regard with this the current review has included the developmental phases for AGEs, complications related with buildup AGEs and inhibitors of protein glycation i.e., synthetic, and natural substances.
Keywords: Advanced glycation end products; Antiglycation; Protein glycation; Chronic diseases